Promosi Kesehatan dengan Buku KIA Terhadap Peningkatan Pengetahuan Ibu Hamil dan Ante Natal Care Di Puskesmas Ceper Klaten Tahun 2011 - Sumardino Sumardino; Sunarto Sunarto (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Health Promotion, Book KIA, Pengetahuan Antenatal Care. Mother and child health in Indonesia is still a major problem. It can be seen from the maternal mortality rate (MMR) that is still high. According to the extrapolation Central Statistics Agency (BPS) in 2007 MMR at 248 per 100,000 live births, while the MDG's target of 2015 was 102/100.000 KH (Department of Health, 2008). In Klaten district from 2005 to 2008 maternal mortality rate has decreased. In 2005 AKI showed 0.61, by 2006 MMR decreased by 0.47, in 2007, maternal mortality was 1.31, while in 2008 rose to 1.33 in 2009 and decreased to 0.98 (Klaten District Health Profile , 2009). Kesehatan Ibu dan Anak (KIA) is a book containing instruments to record the mother and child health condition, and consists of the guide for health promotion for mothers and their families, as well as a means of communication between health professionals and families. Research Objective is to know the impact of health promotion using books KIA t the increased knowledge and antenatal care to pregnant women in the health centers Ceper. The study was experiment with a survey approach. The study design is one group pre test - post test. Result shows the knowledge level of pregnant women about the Maternal and Child Book in Health Center Ceper Klaten area in 2011 was moderate level before being given a book MCH 28 (56%).After reading the book, the majority of pregnant mother which is 45 (90%) have a high level of knowledge with significance of 0001 and the r value correlation is low (0.389). The knowledge of antenatal care before being given the book at moderate level account 29 (58%) and after being given KIA book, the majority of pregnant mother, 39 (70%) have a high level of knowledge with significance 0:00 and r value 0,441 that means the correlation was moderate.